Effect of Physical Activity on Cognitive Impairment in Patients With Cerebrovascular Diseases: A Systematic Review and Meta-Analysis - Lin, Huawei; Liu, HuanHuan; Dai, Yaling; Yin, Xiaolong; Li, Zuanfang; Yang, Lei; Tao, Jing; Liu, Weilin; Chen, Lidian (Frontiers in Neurology, 2022)
Abstract Background and Purpose: This study aimed to investigate the effect of physical activity (PA) on cognition in patients with cerebrovascular disease and explored the maximum benefit of different PA characteristics. Methods: Pubmed, Web of Science, Embase and Cochrane Library were searched from their inception to May 31, 2021. Standardized mean difference (SMD) and 95% confidence intervals (CI) were calculated to generate forest plot. In addition, subgroup analysis, moderation analysis and regression analysis were performed to explore the possible adjustment factors. Results: 22 studies met the criteria were included, including 1601 participants. The results indicated that PA produced a positive effect on global cognition for patients with cerebrovascular disease (SMD: 0.20 [95% CI: 0.12 to 0.27]), at the same time PA training prominently improved executive function (SMD: 0.09 [95% CI: 0.00 to 0.17]) and working memory (SMD: 0.25 [95% CI: 0.10 to 0.40]). Furthermore, PA prevention and treatment for patients with cerebrovascular disease can improve cognitive impairments (SMD: 0.24 [95% CI: 0.04 to 0.26]; SMD: 0.24 [95% CI: 0.14 to 0.34]). For patients in acute stage (≤3 months), PA did not rescue impairment dysfunction significantly (P>0.05) and remarkable cognitive gains were detected in chronic stage of participants (>3 months) (SMD: 0.25 [95% CI: 0.16 to 0.35]). Moderate intensity PA showed a larger pooled effect size (SMD: 0.23 [95% CI: 0.11 to 0.36]) than low intensity (SMD: -0.01 [95% CI: -0.12 to 0.28]) and high intensity (SMD: 0.16 [95% CI: 0.03 to 0.29]). However, different type, duration and frequency of PA resulted in no differences in the improvement of cognitive function. Further regression analysis demonstrated that the beneficial effects of PA on cognition are negatively correlated with age (P<0.05). Conclusions: This study revealed moderate intensity PA can prominently improve overall cognitive ability in patients with cerebrovascular diseases. These findings strengthened the evidence that PA held promise as a widely accessible and effective non-drug therapy for vascular cognitive impairment.